Osteoinductive low-dose 3D porous calcium phosphate graphene oxide–integrated matrices enhance osteogenesis and mechanical properties - Hosseini, Fatemeh S.; Whitfield, Taraje; Orlando, Jason D.; Deng, Chenyun; Abedini, Amir A.; Argyrou, Chrysoula; Kan, Ho-Man; Ghosh, Debolina; Maye, Peter F.; Lo, Kevin W.-H.; Nair, LakshmiS; Sydlik, Stefanie A.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2025)
Bone regeneration continues to be a challenge due to the complex nature of the tissue. Identifying new materials that stimulate regeneration while providing mechanical properties is an active area of research. One class of promising material in bone regeneration is graphene and its derivatives including graphene oxide (GO), the oxidized form of graphene. Recently, calcium phosphate graphene (CaPG), synthesized from GO, has been proven to have osteoinductive properties in vivo. However, CaPG is a powder, and therefore, processing is difficult. Here, we present a method for creating porous CaPG matrices by incorporating it in poly(lactic-co-glycolic acid) (PLGA). This research has comprehensively evaluated CaPG-encapsulated PLGA-based microspheres for localized delivery of osteoinductive inducerons, calcium, and phosphate ions for bone regenerative engineering. CaPG distribution improved mechanical properties and matrix hydrophilicity. CaPG-integrated matrices successfully supported cell viability, proliferation, and enhanced osteogenic differentiation of MC3T3-E1 cells assessed by alkaline phosphatase activity and calcium deposition. Major osteogenic gene expression significantly increased, including Sp7, bone gamma-carboxyglutamate protein, COL1A1, bone sialoprotein, and dentin matrix protein1. The CaPG-containing matrices induced the endogenous canonical Wnt/β-catenin signaling pathway, with no significant difference when treated with DKK1 inhibition, demonstrating its possible selective activation mechanism. The increased protein expression of pathway-specific target genes, Bone morphogenic protein-2 (BMP-2) and WNT-1-inducible-signaling pathway protein 1 (WISP-1), further confirmed endogenous activation of canonical Wnt/β-catenin signaling. These results suggest that CaPG-modified matrices improve the cellular osteogenic differentiation via the canonical Wnt/β-catenin signaling pathway. This study provides further mechanistic insights into the nature of crosstalk between cells and inducerons-rich functionalized matrices for osteoblastic differentiation and improved bone regeneration.